2001
DOI: 10.1093/cercor/11.11.1083
|View full text |Cite
|
Sign up to set email alerts
|

Visual Mechanisms of Spatial Disorientation in Alzheimer's Disease

Abstract: Impaired optic flow perception may contribute to the visuospatial disorientation of Alzheimer's disease (AD). We find that 36% of AD patients have elevated perceptual thresholds for left/right outward radial optic flow discrimination. This impairment is related to independent visual motion processing deficits affecting the perception of left/right motion-defined boundaries and in/out radial motion. Elevated optic flow thresholds in AD are correlated with greater difficulty in the Road Map test of visuospatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
69
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 65 publications
10
69
0
2
Order By: Relevance
“…In contrast, there was no significant correlation between the MMSE score and spatial navigation score and adding MMSE scores to optic flow threshold in a regression model did not explain more variance in the spatial navigation scores. Another study found significant correlation of the optic flow thresholds also with a score in the table-top left-right orientation Money Road Map test and the ability to respect lane boundaries during sustained driving in On-the-Road Driving test (O'Brien et al, 2001). Rather convincing evidence of the importance of visual perception deficit in spatial disorientation in AD was recently provided in a study by Kavcic et al (2006).…”
Section: Perceptual Deficitsmentioning
confidence: 90%
“…In contrast, there was no significant correlation between the MMSE score and spatial navigation score and adding MMSE scores to optic flow threshold in a regression model did not explain more variance in the spatial navigation scores. Another study found significant correlation of the optic flow thresholds also with a score in the table-top left-right orientation Money Road Map test and the ability to respect lane boundaries during sustained driving in On-the-Road Driving test (O'Brien et al, 2001). Rather convincing evidence of the importance of visual perception deficit in spatial disorientation in AD was recently provided in a study by Kavcic et al (2006).…”
Section: Perceptual Deficitsmentioning
confidence: 90%
“…such as disorientation in a hospital lobby (14), a score in the Money Road Map (MRM) test and the ability to respect lane boundaries during sustained driving in an on-the-road driving test (25). Further studies described results consistent with this theory, such as poor incidental landmark learning instead of proper recognition of landmarks mentioned during the walk (12), or a lack of relationship between disorientation with memory tests and a failure to use spatial architectural information (13).…”
Section: Discussionmentioning
confidence: 99%
“…␤-FNA may also have affected other brain regions and behavioral domains. Although hAPP FAD mice have normal visual acuity, they have difficulty associating a visual cue with escape from water (deIpolyi et al, 2008), an impairment that might relate to visual processing deficits (O'Brien et al, 2001;Kergoat et al, 2002;Mapstone et al, 2003) or topographic agnosia (Kiyosawa et al, 1989;Mendez and Cherrier, 2003) in AD. Although the precise neural substrates of these behavioral deficits are unknown, aberrant activation of -opioid receptors might be involved.…”
Section: Discussionmentioning
confidence: 99%